Analisis Pengaruh Panas pada Baja Kontruksi dengan Pendinginan Air Sungai dan Air Laut terhadap Kekuatan Mekanik - Sutrisno Sutrisno; Azmal Azmal; Joni Rahmadi (Vokasi: Jurnal Publikasi Ilmiah, 2022)
Abstract: Housing, buildings and factories often fire, this can be caused by electric short circuits, explosions of gas stoves. Extinguishing fires can use river water or sea water. This research is expected to get an overview of data about tensile strength, hardness and mechanical properties due to changes in heat temperature and cooling with river water and sea water on steel construction materials with various operational conditions. The materials used are plain reinforcing steel (BJTP), deformed steel and profiled steel (IWF-400) heated in the heating kitchen with variations of 600 , 700 , 800 and 900 , cooled by river and sea water, carried out Vickers tensile strength and hardness test. The results of the tensile test of BJTP increased by 461.55 N/mm2, the highest cooling of river water was 9000C=345.15N/mm2(53.70%), the lowest was 600 =31.13 N/mm2 (4.84 %). The highest deformation was 900℃=345.15 N⁄mm2 (53.70 %), the lowest was 600 =31.13N/mm2 (4.84 %). The highest IWF-400 was 900 =101.32 N/mm2 (18.93 %), the lowest was 600 =10.85 N/mm2(2.03%). Vickers BJTP hardness test is the highest for cooling river water 900 =35.06 HV (41.32%), the lowest is 600 =2.16 HV (2.55%). Deform 900 = 47.28 HV (53.63%), the lowest 600 =3.88 HV (4.40%). IWF-400 900 =15.52 HV (18.89 %), the lowest 600 =1.66 HV (2.02%). As the temperature increases by cooling seawater and river water, the tensile strength and hardness of the vickers also increase